SYSTEM APPROACH TO INTERNAL QUALITY EDUCATION CONTROL - Alexander N. Shkrebko; Inna V. Ivanova (Высшее образование в России)
One of the main conditions of modern education development is continuous improvement of educational quality management. Raising of state and society requirements to specialists“ education, cardinal law reforms and strengthening of state governing and control functions necessitate educational quality management implementation and development. The article describes the experience of system approach to the problem at Yaroslavl State Medical Academy. Internal quality education control system at Yaroslavl State Medical Academy is a part of common quality management system, which is working under supervise of Academy Quality Management Service. Internal quality education control is carried out in several directions: control of educational management efficiency, control of requirements and satisfaction of internal and external customers, control of educational programs, control of preparation, organization and realization of educational process, students’ research and extracurricular activities and resources supply of main processes. Some of these processes are described in the article.